De novo synthesis of a sunscreen compound in vertebrates - Osborn, Andrew R; Almabruk, Khaled H; Holzwarth, Garrett; Asamizu, Shumpei; LaDu, Jane; Kean, Kelsey M; Karplus, P Andrew; Tanguay, Robert L; Bakalinsky, Alan T; Mahmud, Taifo (eLife, 2015)
Ultraviolet-protective compounds, such as mycosporine-like amino acids (MAAs) and related gadusols produced by some bacteria, fungi, algae, and marine invertebrates, are critical for the survival of reef-building corals and other marine organisms exposed to high-solar irradiance. These compounds have also been found in marine fish, where their accumulation is thought to be of dietary or symbiont origin. In this study, we report the unexpected discovery that fish can synthesize gadusol de novo and that the analogous pathways are also present in amphibians, reptiles, and birds. Furthermore, we demonstrate that engineered yeast containing the fish genes can produce and secrete gadusol. The discovery of the gadusol pathway in vertebrates provides a platform for understanding its role in these animals, and the possibility of engineering yeast to efficiently produce a natural sunscreen and antioxidant presents an avenue for its large-scale production for possible use in pharmaceuticals and cosmetics. Sunlight is the Earth's primary energy source and is exploited by an array of natural and man-made processes. Photosynthetic plants harness solar energy to convert carbon dioxide and water into biomass, and solar panels capture light and convert it to electricity. Sunlight is critical to life on Earth, and yet excessive exposure to sunlight can cause serious harm as it contains ultraviolet (UV) radiation, which damages the DNA of cells. In humans, this damage can lead to conditions such as cataracts and skin cancer. The marine organisms and animals that live in the upper ocean and on reefs are subject to intense and unrelenting sunlight. In their effort to protect against potentially deadly UV radiation, many small and particularly vulnerable marine organisms, such as bacteria and algae, produce UV-protective sunscreens. While UV-protective compounds have also been found in larger organisms, including fish and their eggs, the presence of these sunscreens has always been attributed to the animal sequestering the compounds from their environment or partnering with a sunscreen-producing microorganism. Now, Osborn, Almabruk, Holzwarth et al. have discovered a fish that is able to produce such a UV-protective compound completely on its own. After identifying the full set of genes—or pathway—responsible for generating the UV-protective compound, the same pathway was detected in a variety of diverse animals, including amphibians, reptiles, and birds. This opens up a new area of study, because besides providing UV protection, no one yet knows what other roles the molecule may have in these animals. Furthermore, introducing the complete pathway into yeast enabled these cells to produce the sunscreen. In the future, engineering a yeast population to produce large quantities of the natural sunscreen could lead to large-scale production of the UV-protective compound so it can be used in pharmaceuticals and cosmetics.